Towards Precision Medicine in Clinical Practice: Alinity C vs. UHPLC-MS/MS in Plasma Aripiprazole Determination - Francisco José Toja-Camba; Enrique Bandín-Vilar; Gonzalo Hermelo-Vidal; Carolina Feitosa-Medeiros; Antonio Cañizo-Outeiriño; Ana Castro-Balado; Iria Varela-Rey; Irene Zarra-Ferro; Anxo Fernández-Ferreiro; Cristina Mondelo-García (MDPI AG, 2024)
Therapeutic drug monitoring improves the benefit-risk balance of antipsychotic therapy. Ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) is considered the gold-standard method for measuring plasma drug concentrations; however, the Alinity C system has emerged as a promising alternative. This is the first study aimed at comparing UHPLC-MS/MS versus Alinity C in measuring plasma concentrations of aripiprazole and dehydroaripiprazole. A total of 86 plasma samples were analyzed. The active moiety of aripiprazole was measured in 60 samples using both systems and 26 samples were analyzed twice using Alinity C with an intermediate period of 6 months to assess its reproducibility. Spearman's correlation revealed a good association between the two assays (rs = 0.96) and no significance differences were found by McNemar's test when classifying samples between infra-, supra- and therapeutic ranges. Passing-Bablock regression showed a good correlation among methods (rs = 0.93) and a slope of 1.12 indicating a slight tendency of Alinity C to measure higher values than UHPLC-MS/MS. In addition, a good intra-method correlation across the two sequential analyses with Alinity C was obtained (rs = 0.99). Nonetheless, clinical decisions could be different in 15% of the cases depending on the chosen method. No differences were found in active moiety determination by Alinity C depending on the concentration of aripiprazole and dehydroaripiprazole of the samples.